Inoculation effects on root-colonizing arbuscular mycorrhizal fungal communities spread beyond directly inoculated plants - Janoušková, Martina; Krak, Karol; Vosátka, Miroslav; Püschel, David; Štorchová, Helena (PLoS One, 2017)
Inoculation with arbuscular mycorrhizal fungi (AMF) may improve plant performance at disturbed sites, but inoculation may also suppress root colonization by native AMF and decrease the diversity of the root-colonizing AMF community. This has been shown for the roots of directly inoculated plants, but little is known about the stability of inoculation effects, and to which degree the inoculant and the inoculation-induced changes in AMF community composition spread into newly emerging seedlings that were not in direct contact with the introduced propagules. We addressed this topic in a greenhouse experiment based on the soil and native AMF community of a post-mining site. Plants were cultivated in compartmented pots with substrate containing the native AMF community, where AMF extraradical mycelium radiating from directly inoculated plants was allowed to inoculate neighboring plants. The abundances of the inoculated isolate and of native AMF taxa were monitored in the roots of the directly inoculated plants and the neighboring plants by quantitative real-time PCR. As expected, inoculation suppressed root colonization of the directly inoculated plants by other AMF taxa of the native AMF community and also by native genotypes of the same species as used for inoculation. In the neighboring plants, high abundance of the inoculant and the suppression of native AMF were maintained. Thus, we demonstrate that inoculation effects on native AMF propagate into plants that were not in direct contact with the introduced inoculum, and are therefore likely to persist at the site of inoculation.
Keywords: mycelium; kořeny rostlin; mykorhiza; Genotype; půda; rostliny; Mycelium; Plant Roots; Seedlings; Soil; Mycorrhizae; genotyp; semenáček; Plants